PHYSICAL COMPOSITION OF KUB CHICKEN CARCASSES GIVEN WITH DRAGON FRUIT PEEL EXTRACT THROUGH DRINKING WATER - N. I. S., Rahayu,; Dewi, G. A. M. K.; Sriyani, N. L. P. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
KUB chicken in addition to being a meat producer also has a high economic value if the carcass production is high. This study aims to determine the physical composition of KUB chicken carcasses given dragon fruit peel extract through drinking water. This research was conducted for 8 weeks at the Teaching Farm of the Faculty of Animal Husbandry, Udayana University, located at Jalan Raya Sesetan, Gang Markisa Denpasar. The research design used was a completely randomized design (CRD) consisting of four treatments and four replicates, each replicate containing five KUB chickens. The treatments were drinking water without dragon fruit peel extract (P0/control); drinking water with 3% dragon fruit peel extract (P1); drinking water with 6% dragon fruit peel extract (P2); drinking water with 9% dragon fruit peel extract (P3). The observed variables were carcass weight and percentage of carcass physical composition (bone, meat, skin and subcutaneous fat). The results showed that the carcass weight variable in the 3%, 6% and 9% treatments showed a significant difference (P<0.05), but had no significant effect (P>0.05) on the percentage of bone, percentage of meat and percentage of skin and subcutaneous fat. Based on the results of the study, it can be concluded that giving dragon fruit peel extract at 3%, 6%, 9% levels can increase carcass weight and does not affect the percentage of bone, meat, skin and subcutaneous fat.